Infections and immune dysregulation in ataxia-telangiectasia children with hyper-IgM and non-hyper-IgM phenotypes: A single-center experience - Szczawińska-Popłonyk, Aleksandra; Tąpolska-Jóźwiak, Katarzyna; Schwartzmann, Eyal; Pietrucha, Barbara (Frontiers in Pediatrics, 2022)
Ataxia-telangiectasia (A-T) is a severe syndromic neurodegenerative inborn error of immunity characterized by DNA reparation defect, chromosomal instability, and hypersensitivity to ionizing radiation, thereby predisposing affected individuals to malignant transformation. While the leading disease symptomatology is associated with progressively debilitating cerebellar ataxia accompanied by central and peripheral nervous system dysfunctions, A-T is a multisystemic disorder manifesting with the heterogeneity of phenotypic features. These include airway and interstitial lung disease, chronic liver disease, endocrine abnormalities, and cutaneous and deep-organ granulomatosis. The impaired thymic T cell production, defective B cell development and antibody production, as well as bone marrow failure, contribute to a combined immunodeficiency predisposing to infectious complications, immune dysregulation, and organ-specific immunopathology, with the A-T hyper-IgM (HIGM) phenotype determining the more severe disease course. This study aimed to clarify the immunodeficiency and associated immune dysregulation as well as organ-specific immunopathology in children with A-T. We also sought to determine whether the hyper-IgM and non-hyper-IgM phenotypes play a discriminatory role and have prognostic significance in anticipating the clinical course and outcome of the disease. We retrospectively reviewed the medical records of twelve A-T patients, aged from two to eighteen years. The patients' infectious history, organ-specific symptomatology, and immunological workup including serum alpha-fetoprotein, immunoglobulin isotypes, IgG subclasses, and lymphocyte compartments were examined. For further comparative analysis, all the subjects were divided into two groups, HIGM A-T and non-HIGM A-T. The clinical evaluation of the study group showed that recurrent respiratory tract infections due to viral and bacterial pathogens and a chronic obstructive airway disease along with impaired humoral immunity, in particular complete IgA deficiency, were noted in all the A-T patients, with both HIGM and non-HIGM phenotypes. The most important features with the discriminatory role between groups, were autoimmune disorders, observable four times more frequently in HIGM than in non-HIGM A-T. Two patients with the HIGM A-T phenotype were deceased due to liver failure and chronic Epstein-Barr virus (EBV) infection. It may therefore be assumed that the HIGM form of A-T is associated with more profound T cell dysfunction, defective immunoglobulin class switching, chronic EBV expansion, and poorer prognosis.